THE INTEGRATION AND THE BENEFITS OF TECHNOLOGIES IN LANGUAGE LEARNING (Web of Teachers: Inderscience Research, 2025)
This article explores the various ways technology has transformed language education, including the benefits of digital tools, the challenges they present, and how learners and educators can effectively harness these technologies. It also examines key innovations such as gamified learning, virtual reality (VR), and artificial intelligence (AI) in language learning, and highlights the role of online communities in supporting second language acquisition.